Pathophysiology and Pharmacotherapy of Cardiovascular Disease - Jagadeesh, Gowraganahalli; Balakumar, Pitchai; Maung-U, Khin.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis, 2015)
The present book covers the basic principles of cardiovascular physiology, pathophysiology and advanced pharmacology with particular emphasis on cellular mechanisms of drug action. It provides an update on the progress made in several aspects of cardiovascular diseases so that it might kindle scientists and clinicians alike in furthering basic and translational research. In addition, the book is expected to fill imperative gaps in understanding and optimally treating cardiovascular disease.
Heart Failure -- Cardiac Hypertrophy -- Cardiac Arrhythmias -- Valvular Heart Disease -- Coronary Heart Disease -- Management of Pericarditis -- Hypertension -- Atherosclerosis and hyperlipidemia -- Cardiovascular Conditions of Childhood -- Sudden Cardiac Death -- Peripheral artery disease.
Keywords: Cardiology; Pharmacotherapy; Pharmacology; Cardiology; Pharmacotherapy; Pharmacology/Toxicology.